Economics of development and planning (with special reference to India) - Jhingan, M.L. (New Delhi, 1982)
The present edition has been tho roughly revised and updated with the latest available data and mate rial from various Indian and foreign journals, and private and official sources. Many chapters have been rewritten. Two new chapters relating to Malthus's Theory and Mill's Theory of Economic Development have been added to Part Two of the book. Besides, seven new chapters relating to Planning in India have been added to Part Seven. They are: National Income; Saving, Investment and Growth Rates; The Pattern of Investment in Indian Plans; Foreign Trade in India; Planned Growth with Social Justice; Technique and Methodology of Planning in India: and Planning Machinery in India.
Keywords: Economic development